Strengthening access to finance for women-owned SMEs in developing countries - Ahmad, Syed Zamberi; Muhammad Arif, Afida Mastura (Emerald Group Publishing, 2015)
Purpose: The purpose of this paper is to highlight key trends, challenges, and opportunities for advancing women’s entrepreneurship and increasing their access to finance. Design/methodology/approach: Due to their high-growth potential, women-owned SMEs in developing countries are of particular interest. The International Financial Corporation and McKinsey built a detailed database for micro-, small-, and medium-sized enterprises. The data derived from the readily available global data sets provide coverage of a large number of countries and national statistics. Findings: Since financing is an important means by which to pursue growth opportunities, addressing the specific needs of women entrepreneurs (WE) in accessing finance must be part of the development agenda. Practical implications: This paper offers valuable practical insights to policy makers to establish a supportive, enabling environment that will facilitate access to financial services for WE in their respective countries; lead efforts to identify, evaluate, and support the replication of successful models for expanding financial services to WE; and lead efforts to gather gender-disaggregated data on small-, and medium-sized enterprise finance in a coordinated fashion. Originality/value: The value of this paper is that it offers insightful information about key trends, challenges, and opportunities for advancing women’s entrepreneurship and increasing their access to finance.